Regiodivergent Synthesis of Oxadiazocines via Dirhodium-Catalyzed Reactivity of Oxazolidines and α-Imino Carbenes - Viudes, Olivier; Guarnieri-Ibáñez, Alejandro; Besnard, Céline; Lacour, Jérôme (Synlett, 2023)
Using electron-rich or electron-poor N-substituted oxazolidines as substrates, selective formation of either ammonium or oxonium ylides is possible in the presence of α-imino carbenes. As such, treatment of 5-membered oxazolidine precursors with N-sulfonyl-1,2,3-triazoles under dirhodium catalysis (2 mol%) affords the regiodivergent synthesis of either 8-membered 1,3,6- or 1,4,6-oxadiazocines upon the initial N or O reactivity with the carbene.
Keywords: carbenes; diazaoxa heterocycles; 8-membered rings; regiodivergency; Rh(II) catalysis; triazoles; ylides